1977
DOI: 10.1111/j.1600-0447.1977.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorpromazine treatment on prolactin levels in cerebrospinal fluid and plasma of psychotic patients

Abstract: In psychotic patients, levels of prolactin in cerebrospinal fluid (CSF) and plasma were determined by radioimmunoassay before and after 2 and 4 weeks of treatment with chlorpromazine (CPZ). CPZ was given in one of three randomly selected fixed doses: 200, 400 or 600 mg per day. Before treatment, low levels of immunoreactive prolactin-like material (PRL) were found in the CSF of most patients. The concentration in CSF was about 20% of the plasma level. In CSF but not in plasma, the pre-treatment level of PRL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…The study shows no evidence of tolerance in the prolactin response to zotepine, in line with fixeddose studies for chlorpromazine (Wode-Helgodt et al, 1977;Alfredsson er al., 1984), sulpiride (Alfredsson er al., 1984), and haloperidol (Linkowski et al, 1984).…”
Section: Discussionsupporting
confidence: 79%
“…The study shows no evidence of tolerance in the prolactin response to zotepine, in line with fixeddose studies for chlorpromazine (Wode-Helgodt et al, 1977;Alfredsson er al., 1984), sulpiride (Alfredsson er al., 1984), and haloperidol (Linkowski et al, 1984).…”
Section: Discussionsupporting
confidence: 79%
“…They include serotonin, thyrotropin releasing hormone (TRH), histamine, acetyl choline, prostaglandins, GABA, endorphins, encephalins and estrogenic hormones (11,20,30,40,45). The present finding of higher CSF baseline concentrations of PRL in female pa tients is in accordance with the results of W<j>de-Helgodt et al (47), who noted signifi cantly higher CSF PRL pretreatment levels in psychotic women than in equally disturbed male patients. After 2 -4 weeks of chlorpromazine therapy, the authors observed a significantly higher elevation of CSF PRL in female patients than in male patients.…”
Section: Discussionsupporting
confidence: 82%
“…Corre spondingly, a more sensitive PRL response in women than in men has also been demonstrated by Jones et al (19) after administration of chlomipramine to depressed patients. These findings are suggested to be due to estrogeninduced sensitization of the PRL system to psychopharmacological manipulation (36,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46). During acute neuroleptic treatment, the plasma Prl level has been found to be significantly correlated with the serum levels of neuroleptics (31,51,54), but only within a narrow range as there is a maximal Prl response at low doses of neuroleptics, below the therapeutic range (22,34). Another significant correlation between the potency to release Prl and their antipsycho tic property has been reported (22,33).…”
Section: Introductionmentioning
confidence: 86%